FeCl3(Py)4, FeCl3[(NH2)2CO]6 and FeCl3[(NH2)2CS]6 as Efficient Catalysts for the Efficient Reduction of Carbonyl Compounds with NaBH4 under Apr - Haghgooie, Hossein; Zeynizadeh, Behzad; Shafaghi, Maryam (Asian Journal of Chemistry, 2010)
FeCl3(Py)4, FeCl3[(NH2)2CO]6 and FeCl3[(NH2)2CS]6 are used as efficient catalysts for reduction of a variety of carbonyl compounds such as aldehydes, ketones, acyloins, α-diketones and conjugated carbonyl compounds with NaBH4 under aprotic condition. The corresponding alcohols are obtained in high to excellent yields. Reduction reactions are performed in CH3CN at room temperature or reflux.